2011
DOI: 10.1016/j.hkpj.2011.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of electromyographic biofeedback training on quadriceps muscle strength in osteoarthritis of knee

Abstract: The objective of this randomised controlled trial was to evaluate the effectiveness of electromyographic biofeedback as an add-on therapy with isometric exercise on quadriceps strengthening in patients with osteoarthritis of knee. Thirty three, 10 men and 23 women, patients with osteoarthritis of knee participated in the study. Patients were randomly placed into two groups: a biofeedback group (n Z 17) and a control group (n Z 16). The biofeedback group received electromyographic biofeedback-guided isometric e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 18 publications
0
38
1
1
Order By: Relevance
“…On the other hand, in a study in 2011, Anwer et al evaluated the effects of EMGBF on the strength of quadriceps muscles in 33 patients with knee OA who were randomly assigned to two groups of control with 16 subjects and BF with 17 patients, and after 5 weeks of exercise with/without BF, found the maximum isometric strength of the quadriceps muscles to be significantly greater in the BF group compared to the control group ( P =0.004). 35 This is one of the studies whose findings were incompatible with ours. Lepley et al also conducted a systematic review in 2012 in which they showed that EMGBF had significant effects on the isometric strength of quadriceps muscles, but these authors did not limit their inclusion criteria to patients with knee OA.…”
Section: Discussioncontrasting
confidence: 84%
“…On the other hand, in a study in 2011, Anwer et al evaluated the effects of EMGBF on the strength of quadriceps muscles in 33 patients with knee OA who were randomly assigned to two groups of control with 16 subjects and BF with 17 patients, and after 5 weeks of exercise with/without BF, found the maximum isometric strength of the quadriceps muscles to be significantly greater in the BF group compared to the control group ( P =0.004). 35 This is one of the studies whose findings were incompatible with ours. Lepley et al also conducted a systematic review in 2012 in which they showed that EMGBF had significant effects on the isometric strength of quadriceps muscles, but these authors did not limit their inclusion criteria to patients with knee OA.…”
Section: Discussioncontrasting
confidence: 84%
“…These variables were measured using the Numerical Rating Scale (NRS)14, 15 ) , a reduced WOMAC index16, 17 ) , and a strength gauge device18,19,20,21 ) , respectively. All the measurements were taken at baseline (week 0) and at the end of the trial at week 5.…”
Section: Methodsmentioning
confidence: 99%
“…The outcome measures or dependent variables selected for this study were pain intensity, knee function, and isometric quadriceps strength. These variables were measured using the Numerical Rating Scale (NRS) 14 , 15 ) , a reduced WOMAC index 16 , 17 ) , and a strength gauge device 18 , 19 , 20 , 21 ) , respectively. All the measurements were taken at baseline (week 0) and at the end of the trial at week 5.…”
Section: Methodsmentioning
confidence: 99%
“…Another approach to observing movements is to use biofeedback devices that transform sensor measurements from the body into sound, a blinking LED, or an observable shape on a screen [28][29][30]. Biofeedback provides detailed information regarding the lengthening, shortening, and physical exertion of a muscle.…”
Section: Introductionmentioning
confidence: 99%